(untitled) (Journal of Parents and Teachers, 2014)
The following article deals with a teenager who experience Christmas without his family. The author analyzes and reflects about the relationship with his relatives, when a person is very far from his or her home. Everything is viewed from an experienced and thoughtful perspective about this familiar period that is Christmas.